EVALUATION OF THE ATTITUDE OF CITY RESIDENTS TO IMMIGRANT STUDENTS: EMPIRICAL ANALYSIS - Zhelnina, E.V; Payramova, I.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article deals with the actual problem of modern society, the main characteristic of which is the globalization of all processes taking place in it, including education. In addition, the publication presents the results of the author's sociological study of the attitude of Togliatti students to immigrant students, conducted using the method of unfinished sentences (N=30), held in may 2019. The purpose of the author's sociological research is to study the attitude of Togliatti students to immigrant students. The use of the method of unfinished sentences is justified by the fact that based on the analysis of the respondents ' interpretations it is possible to determine the subjective inclinations and attitudes of young people in relation to students who came to Togliatti from other regions in order to get an education. Among the students interviewed by us-Togliatti most of nothing against the presence of visiting students does not have, on the contrary, wants them to be more. In most cases, there is no social tension between Togliatti students and visiting students. In General, the attitude towards visiting students in groups is positive. Most respondents noted the positive impact of visiting students at the University. The analysis of the situation showed that to keep visiting students (and in the future personnel specialists) in Togliatti, it is necessary to create conditions that would help them to improve the quality and standard of living, as well as to increase the number of job offers with further career prospects.